Histomorphometric assessment of bone necrosis produced by two cryosurgery protocols using liquid nitrogen: an experimental study on rat femurs - Fábio Wildson Gurgel Costa; Gerly Anne de Castro Brito; Rosana Maria Andrade Pessoa; Eduardo Costa Studart-Soares (University of São Paulo, 2011)
OBJECTIVE: The aim of this study was to evaluate the effects of liquid nitrogen cryosurgery on the femoral diaphysis of rats. MATERIAL AND METHODS: The femoral diaphyses of 42 Wistar rats were exposed to three local and sequential applications of liquid nitrogen for 1 or 2 min, intercalated with periods of 5 min of passive thawing. The animals were sacrificed after 1, 2, 4 and 12 weeks and the specimens obtained were processed and analyzed histomorphometrically. RESULTS: The depth and extent of peak bone necrosis were 124.509 µm and 2087.094 µm for the 1-min protocol, respectively, and 436.424 µm and 12046.426 µm for the 2-min protocol. Peak necrosis was observed in the second experimental week with both cryotherapy protocols. CONCLUSIONS: The present results indicate that the 2-min protocol produced more marked bone necrosis than the 1-min protocol. Although our results cannot be entirely extrapolated to clinical practice, they contribute to the understanding of the behavior of bone tissue submitted to different cycles of liquid nitrogen freezing and may serve as a basis for new studies.